30‐2: A Low Voltage Blue Phase Liquid Crystal Spatial Light Modulator. Issue 1 (May 2016) - Peng, Fenglin; Lee, Yun‐Han; Luo, Zhenyue; Wu, Shin‐Tson
Abstract : A novel device configuration allowing the incident beam to traverse the blue phase liquid crystal (BPLC) layer four times in an LCoS spatial light modulator is demonstrated. The operation voltage for achieving 2‐pi phase change is < 24V. This approach enables BPLC to be implemented in high resolution LCoS for widespread applications.